Dinamika Pergeseran Bahasa Dalam Masyarakat: Pengaruh Media Sosial Terhadap Kesantunan Berbahasa Jawa Krama di Desa Sumbarang Kecamatan Jatinegara Kabupaten Tegal - Maesiyah, Mahdatul; Sasea, Sanita Carolina; Raisyabilla, Rangga Octava (DISCOURSE: Indonesian Journal of Social Studies and Education, 2025)
Modernization and globalization have brought significant changes in the social life of the community, including in the aspect of language and communication. Sumbarang Village, Jatinegara Subdistrict, Tegal Regency, is one of the villages that still maintains its local wisdom, especially in the use of Javanese manners as a form of politeness in communication. However, the widespread influence of social media has caused a language shift that leads to a decrease in the use of Javanese manners, especially among the younger generation. This study aims to analyze how the use of social media affects changes in the communication patterns of the people of Sumbarang Village and the extent to which language shifts occur in everyday life. Using a qualitative approach with in-depth observation and interview methods, this study found that the use of social media accelerates the influx of informal language as well as new terms that replace traditional forms of communication. Children and teenagers are using Javanese manners less and less in their daily conversations, even with their parents. This is influenced by exposure to Indonesian and slang which are more dominant in digital interactions. This research shows that language shift is not just a linguistic phenomenon, but also reflects changes in cultural values and identity. Therefore, there needs to be an effort to revitalize Javanese manners through education and local communities so that language politeness remains part of the identity of the people of Sumbarang Village.